"Inflammaging" and Estradiol among Older U.S. Women: A Nationally Representative Longitudinal Study. (2nd October 2017) - Das, Aniruddha
ABSTRACT: Despite accumulating small-sample and clinical evidence on "inflammaging, " no population-representative longitudinal studies have specifically examined women's late-life inflammation trends. While a range of studies indicates estradiol's immunomodulation role, evidence is contradictory on whether its effects are pro- or antiinflammatory among older women. Using longitudinal data from the first two waves of the National Social Life, Health and Aging Project—a national probability sample of older U.S. adults aged 57 to 85 years at baseline—this study began to fill these gaps. Findings suggested rather than being a lifelong process, older women's inflammaging may have a biological window that closes with senescence. Moreover, their endogenous estradiol plays a proinflammatory rather than immunoprotective role. Nor does this sex steroid modulate age effects on women's inflammation. More sex-specific basic research is needed on causal mechanisms underlying women's late-life inflammaging patterns.